2020
DOI: 10.1002/cam4.3305
|View full text |Cite
|
Sign up to set email alerts
|

Association of sonographic features and molecular subtypes in predicting breast cancer disease outcomes

Abstract: Background Features in preoperative ultrasound could predict the prognosis of triple‐negative breast cancer (TNBC), while its prognostic value in other molecular subtypes of breast cancer (BC) was unknown. The study aimed to assess the prognostic value of preoperative sonographic features, including orientations, on long‐term outcomes in BC and its association with different molecular subtypes. Methods Women diagnosed with invasive BC > 5 mm who underwent surgery were retrospectively reviewed. Clinical, pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…In this task, the great majority of cases were HER2 negative, constituting 62.22% of patients, while only 22.22% were HER2 positive. This was similar to the findings of Wang et al who found that HER2 was negative in 76.8%, while it was positive in 23.2% [82]. These values also agree with several studies [41,43,76,83].…”
Section: Luminal Her2 + Triple Negative Missingsupporting
confidence: 93%
“…In this task, the great majority of cases were HER2 negative, constituting 62.22% of patients, while only 22.22% were HER2 positive. This was similar to the findings of Wang et al who found that HER2 was negative in 76.8%, while it was positive in 23.2% [82]. These values also agree with several studies [41,43,76,83].…”
Section: Luminal Her2 + Triple Negative Missingsupporting
confidence: 93%
“…The characteristic of vertical growth represents a sign that carcinoma cells can easily destroy normal breast tissue growing orienting skin and have highly aggressive characteristics and a grave prognosis [ 27 ]. Wang et al found that nonparallel growth orientation was similar to molecular subtypes on the prognostic values for BC and can be served as a prognostic biomarker for triple negative BC patients [ 28 ]. Our previous study also demonstrated that the vertical growth orientation of a tumor in preoperative US examination was associated with a high recurrence risk of BC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%